PpHYH is responsible for light-induced anthocyanin accumulation in fruit peel of Prunus persica. (26th February 2022) - Zhao, Lei; Sun, Juanli; Cai, Yaming; Yang, Qiurui; Zhang, Yuanqiang; Ogutu, Collins Otieno; Liu, Jingjing; Zhao, Yun; Wang, Furong; He, Huaping; Zheng, Beibei; Han, Yuepeng
Abstract: Peach Prunus persica is an economically important fruit tree crop worldwide. Although the external color of fruit is an important aspect of fruit quality, the mechanisms underlying its formation remain elusive in peach. Here, we report an elongated hypocotyl 5-homolog gene PpHYH involved in the regulation of anthocyanin pigmentation in peach fruit peel. Anthocyanin accumulation in fruit peel is light-dependent in peach. PpHYH had no auto-activation activity and its transcription was induced by sunlight. PpHYH activated transcription of a cluster of three PpMYB10 genes in the present of a cofactor PpBBX4 encoding a B-BOX protein, leading to anthocyanin accumulation in the sun-exposed peel. However, the PpHYH activity was repressed by a negative regulator of PpCOP1 encoding constitutive photomorphogenesis protein 1 which accumulated in the nucleus under dark condition, resulting in failure of anthocyanin accumulation in the shaded peel. PpCOP1 was re-localized into the cytosol under light condition, in accordance with fruit peel pigmentation. Additionally, transport of anthocyanins from the cytoplasm to the vacuole was a rate-limiting step for anthocyanin accumulation in peach fruit peel. Our results reveal for the first time the HYH gene involved in the regulation of anthocyanin accumulation in fruits, and provide target genes for genetic manipulation of fruit coloration.